2019
DOI: 10.3390/e21090856
|View full text |Cite
|
Sign up to set email alerts
|

Crystallisation in Melts of Short, Semi-Flexible Hard-Sphere Polymer Chains: The Role of the Non-Bonded Interaction Range

Abstract: A melt of short semi-flexible polymers with hard-sphere-type non-bonded interaction undergoes a first-order crystallisation transition at lower density than a melt of hard-sphere monomers or a flexible hard-sphere chain. In contrast to the flexible hard-sphere chains, the semi-flexible ones have an intrinsic stiffness energy scale, which determines the natural temperature scale of the system. In this paper, we investigate the effect of weak additional non-bonded interaction on the phase transition temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In spite of the granular, colloidal, or droplet polymers being significantly less well explored than the “traditional” ones, over the years, there have been significant advances in their synthesis and characterization [ 61 , 62 , 63 , 64 , 65 ]. From the perspective of theory and simulation [ 66 , 67 ], emphasis is placed on the phase transition of semi-flexible [ 68 , 69 , 70 ] or flexible [ 71 , 72 ] chains of hard spheres, while recently, it was demonstrated that the use of block copolymers leads to HCP stable phases [ 73 , 74 , 75 ]. The stabilization of HCP colloidal structures has been investigated through the insertion of polymers [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the granular, colloidal, or droplet polymers being significantly less well explored than the “traditional” ones, over the years, there have been significant advances in their synthesis and characterization [ 61 , 62 , 63 , 64 , 65 ]. From the perspective of theory and simulation [ 66 , 67 ], emphasis is placed on the phase transition of semi-flexible [ 68 , 69 , 70 ] or flexible [ 71 , 72 ] chains of hard spheres, while recently, it was demonstrated that the use of block copolymers leads to HCP stable phases [ 73 , 74 , 75 ]. The stabilization of HCP colloidal structures has been investigated through the insertion of polymers [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…These alternating layers possess a unique stacking direction and are free of twin defects, as the latter are incompatible with the entropic barriers imposed by chain connectivity [ 15 ]. The critical phase transition of hard-sphere chains is heavily affected by factors, such as bond gaps [ 16 , 17 ] and/or chain stiffness [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization or solidification of hard-sphere chains in the bulk has been reported in the literature, considering as the influence of chain length, backbone stiffness, and bond geometry [ 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], and highlighting similarities and differences with respect to the crystal nucleation and growth of monomeric analogs [ 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. The jamming or phase transition of athermal, initially random packings, both of monomers and of chains, under confinement have not been studied as extensively as the bulk case, but independent works have provided significant insights over the years [ 3 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and modeling works are of major importance in the study of crystallization of hard sphere chains [68,69]. From the perspective of simulation, emphasis is placed on the phase transition of semi-flexible [70][71][72] or flexible [73,74] chains of hard spheres, while recently it was demonstrated that the use of block copolymers leads to HCP stable phases [75][76][77]. The stabilization of HCP colloidal structures has been investigated through insertion of polymers [78,79].…”
Section: Introductionmentioning
confidence: 99%